Artificial Light at Night of Different Spectral Compositions Differentially Affects Tumor Growth in Mice: Interaction With Melatonin and Epigenetic Pathways. (23rd November 2018) - Zubidat, A. E.; Fares, B.; Fares, F.; Haim, A.
Lighting technology is rapidly advancing toward shorter wavelength illuminations that offer energy-efficient properties. Along with this advantage, the increased use of such illuminations also poses some health challenges, particularly breast cancer progression. Here, we evaluated the effects of artificial light at night (ALAN) of 4 different spectral compositions (500-595 nm) at 350 Lux on melatonin suppression by measuring its urine metabolite 6-sulfatoxymelatonin, global DNA methylation, tumor growth, metastases formation, and urinary corticosterone levels in 4T1 breast cancer cell-inoculated female BALB/c mice. The results revealed an inverse dose-dependent relationship between wavelength and melatonin suppression. Short wavelength increased tumor growth, promoted lung metastases formation, and advanced DNA hypomethylation, while long wavelength lessened these effects. Melatonin treatment counteracted these effects and resulted in reduced cancer burden. The wavelength suppression threshold for melatonin-induced tumor growth was 500 nm. These results suggest that short wavelength increases cancer burden by inducing aberrant DNA methylation mediated by the suppression of melatonin. Additionally, melatonin suppression and global DNA methylation are suggested as promising biomarkers for early diagnosis and therapy of breast cancer. Finally, ALAN may manifest other physiological responses such as stress responses that may challenge the survival fitness of the animal under natural environments.